PENGARUH PEMBERIAN EKSTRAK TEPUNG ROSELA (Hibiscus sabdarifa Linn) TERHADAP SIFAT FISIK DAN KIMIA DENDENG BABI (The effect of roselle flour extract (hibiscus sabdariff linn) on the physical and chemical characteristics of pork jerky) - Rita Dapamawu; gemini malelak; Pieter Rihi Kale (JURNAL NUKLEUS PETERNAKAN, 2021)
This study aimed was to determine the effect of roselle flour extract on pork jerky. Completely randomized design 4 x 3 was used in this experiment The treatment consisted of ER0 = without addition of roselle flour extract, ER4 = 4% (v/w) roselle flour extract, ER8 = roselle flour extract 8% (v/w) and ER12 = roselle flour extract 12%(v/w). The parameters observed were water content, fat oxidation, total bacteria, ph and organoleptic: color, aroma, and taste of park jerky. The result of statistical analysis showed that rosela flour exract on pork jerky had highly significantly effect (P<0.01) on water, fat oxidation, pH and organoleptics: colors, the aroma of pork jerky. The lowest water content was in ER12 (35.86±0.33), the lowest fat oxidation was in the ER12 (9.57±0.70), the lowest pH was in ER4 (4.79±0.05). The best color was found in ER4 (4.86±0.38), the best aroma was found in ER0 (5.00±0.00). In conclusion, increasing of roselle flour extract level causes the decreasing the oxidation fat, reducing the color score ( jerky become brown) and rosela/ sour in aroma.